Identification of Corynebacterium pseudotuberculosis from sheep by PCR-restriction analysis using the RNA polymerase β-subunit gene (rpoB) - Pavan, María Elisa (2012)
Caseous lymphadenitis, caused by Corynebacterium pseudotuberculosis, has a high prevalence in many regions of the world, including Argentina and Brazil. A polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method for the identification of this microorganism was designed based on the hypervariable region of the polymorphic RNA polymerase β-subunit gene (rpoB). All available Corynebacterium rpoB sequences were analyzed by computer-assisted restriction analysis. The rpoB PCR-RFLP pattern predicted by using endonucleases MseI and StuI clearly differentiated C. pseudotuberculosis from sixty-one other Corynebacterium species. This method was successfully applied to identify twelve wild C. pseudotuberculosis ovine isolates and one caprine isolate. It was also used to differentiate C. pseudotuberculosis from Arcanobacterium pyogenes, an ovine pathogen with similar clinical characteristics. These results indicate that this new molecular method can be used for the reliable identification of the pathogen, essential for the timely detection of infected animals and for epidemiological studies. © 2011 Elsevier Ltd.